Formulation and Evaluation of Polyherbal Face Pack - Kale Aishwarya Yuvraj,; Namrata S Ghorpade,; Alisha N Sayyad,; Karishma S Shaikh, (Asian Journal of Pharmaceutical Research and Development, 2026)
In recent years, the use of herbal products and natural ingredients has gained worldwide popularity because of their safety and reduced side effects compared to synthetic products. People increasingly prefer herbal medicines and natural cosmetic products for maintaining health and improving skin appearance. Herbal cosmetics are formulations that contain bioactive compounds obtained from medicinal plants and herbs. These herbal ingredients not only enhance the appearance of the skin but also provide essential nutrients required for maintaining healthy skin and improving its biological functions. The present project was undertaken to formulate and evaluate a polyherbal face pack prepared using herbal ingredients for cosmetic purposes. Herbal formulations have emerged as a safer and effective alternative for managing various skin problems without causing harmful effects. Skin conditions such as acne, pimples, blackheads, dark circles, pigmentation, and scars are commonly observed among individuals, especially among young people. According to Ayurveda, many skin disorders occur due to impurities in the blood caused by unhealthy dietary habits and lifestyle choices. The herbal paste known as “Mukha Lepa” has traditionally been used for the treatment and improvement of skin conditions. Different skin types require different formulations to provide proper nourishment and maintain healthy skin. Therefore, herbal face packs can serve as a natural, effective, and economical approach to skin care.